2018
DOI: 10.1016/j.jval.2018.06.017
|View full text |Cite|
|
Sign up to set email alerts
|

Methodological Issues in Assessing the Economic Value of Next-Generation Sequencing Tests: Many Challenges and Not Enough Solutions

Abstract: Background Clinical use of next-generation sequencing (NGS) tests has been increasing, but few studies have examined their economic value. Several studies have noted that there are methodological challenges to conducting economic evaluations of NGS tests. Objective Our objective was to examine key methodological challenges for conducting economic evaluations of NGS tests, prioritize these challenges for future research, and identify how studies have attempted solutions to address these challenges. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…Although diagnostic procedures represent a small proportion of total pathway costs, growing attention has been paid to the impact of NGS on the budget and its cost-effectiveness compared to the standard single-testing approach. Three recent papers on economic studies on NGS have raised concerns on the way cost analyses have been carried out [4][5][6]. Furthermore, they revealed that the evidence on NGS costs is quite poor for Europe, and no data exist for Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Although diagnostic procedures represent a small proportion of total pathway costs, growing attention has been paid to the impact of NGS on the budget and its cost-effectiveness compared to the standard single-testing approach. Three recent papers on economic studies on NGS have raised concerns on the way cost analyses have been carried out [4][5][6]. Furthermore, they revealed that the evidence on NGS costs is quite poor for Europe, and no data exist for Italy.…”
Section: Discussionmentioning
confidence: 99%
“…A key methodological issue when assessing the value of genomics is the lack of evidence for the personal utility that they generate. 5 As a result, nonhealth and process-related outcomes of genomics are rarely considered in health-care decision-making, 6 which is likely to bias resource allocation decisions. 7 There is real need to better understand individual preferences for GS to (1) value the personal utility benefits generated, (2) predict uptake, and (3) inform health-care priorities based on a composite evaluation of costs and benefits.…”
Section: Introductionmentioning
confidence: 99%
“…While many have argued that medical management implications constitute health-related outcomes and fit within the construct of clinical utility, others consider medical management as an example of an indirect or intermediate non-health related outcome, since a medical management decision, unto itself, does not comprise a health outcome [ 12 , 13 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. While the distinction between health and non-health related outcomes remains important to the task of defining and adjudicating the value of genetic testing [ 67 , 68 , 69 ], it is plausible that both health and non-health related outcomes can be perceived and experienced from both clinical and personal perspectives. There is justification for medical management implications, as an impact of genetic testing that sits at the boundary of health and non-health related outcomes, to be included in both personal and clinical utility constructs.…”
Section: Discussionmentioning
confidence: 99%